Entrepreneurial Concept in Islamic Perspective - Fina Umu Rif Athi; Sedya Santosa; Titis Rosowulan (Universitas Muhammadiyah Enrekang, 2022)
Entrepreneurship that is imbued with Islamic values can become a spirit or spirit in an effort to achieve success so that it will be recorded as a form of servitude to Allah SWT in carrying out his duties as His caliph on earth. The purpose of this research is to analyze the concept of entrepreneurship in an Islamic perspective. This research method uses a type of literature study research with a descriptive approach. The data source for this research consisted of 5 books and 25 journals on Entrepreneurship in Islam. The results of the study are business owners who also act as managers are able to take advantage of business opportunities, take into account various risks by organizing and managing a business and receive income in cash or in other forms. The attention of business people (entrepreneurs) to consumers today is getting bigger due to increasingly fierce competition in business and the assumption that consumers are everything or are called kings and must be based on the best.